Respostas

2014-08-17T14:23:38-03:00
E aí véio,

use a propriedade da exponenciação:

a^{m+n}~\to~a^m\cdot a^n\\\\
a^{-m}~\to~ \dfrac{1}{a^m}

___________________

3^{x-1}-3^x+3^{x+1}=63~~~~.\\
3^x\cdot3^{-1}-3^x+3^x\cdot3^1=63

Agora, pomos x em evidência:

3^x(3^{-1}-1+3^1)=63~~~~~.\\\\
3^x\left( \dfrac{1}{3}-1+3\right)=63\\\\
3^x\cdot \dfrac{11}{3}=63\\\\
3^x=63\cdot\dfrac{3}{11}\\\\
3^x= \dfrac{189}{11}\\\\
log3^x=log \dfrac{189}{11}\\\\
x\cdot log3=log189-log11\\\\
x\cdot 0,477=2,276-1,041\\
x\cdot0,477=1,235\\\\
x= \dfrac{1,235}{0,477}\\\\
\large\boxed{\boxed{x\approx2,589}}.\\.

Tenha ótimos estudos ;D
1 5 1